2018
DOI: 10.1007/s00249-018-1314-2
|View full text |Cite
|
Sign up to set email alerts
|

Ionomer and protein size analysis by analytical ultracentrifugation and electrospray scanning mobility particle sizer

Abstract: By combining analytical ultracentrifugation (AUC) in liquid phase and scanning mobility particle sizer (SMPS) in the gas phase, additional information on the particle size and morphology has been obtained for rigid particles. In this paper, we transfer this concept to soft particles, allowing us to analyze the size and molar mass of the short side chain perfluorosulfonic acid ionomer Aquivion in a dilute aqueous suspension. The determination of the primary size and exact molar mass of this class of polymers is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
1
11
1
Order By: Relevance
“…From the diameter of 7− 8 nm, measured for the Aquivion ionomer in water for concentrations up to 2 g/L by analytical ultracentrifugation and by electrospray surface mobility particle sizing, it can be concluded that the Aquivion molecules of our study are not aggregated. 32 Thus, the missing ionomer aggregation explains the deviation of our findings from the prediction given by Mashio et al…”
Section: ■ Results and Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…From the diameter of 7− 8 nm, measured for the Aquivion ionomer in water for concentrations up to 2 g/L by analytical ultracentrifugation and by electrospray surface mobility particle sizing, it can be concluded that the Aquivion molecules of our study are not aggregated. 32 Thus, the missing ionomer aggregation explains the deviation of our findings from the prediction given by Mashio et al…”
Section: ■ Results and Discussionmentioning
confidence: 67%
“…Carbon black is known for its defect-rich surface 39,40 and ionomers have a broad distribution in their molar mass. 32,41 However, at least for low ionomer concentrations, the model reproduces the measured adsorption isotherms reasonably well. It gives values for the plateau concentration and the association constant, which allow a quantitative comparison for different carbon black/ionomer systems and are required for any kind of parameter study.…”
Section: ■ Results and Discussionmentioning
confidence: 69%
“…Thus, an effective optical model representing at best the optical properties of the macroscopic sample must be employed. The concept of effective quantities is common for particle size analysis 23 , 55 , e.g. for the description of particle sizes of nonspherical particles via equivalent volumes.…”
Section: Discussionmentioning
confidence: 99%
“…All these approaches and particle systems require the proper description of higher dimensional property distributions: It is clear that 1D particle size distributions (PSDs) are insufficient for a full and comprehensive understanding of these systems. In the 1D space, nonspherical particles are typically described by equivalent size parameters such as the volume equivalent diameter, diameter of equal volume‐specific surface area, or the hydrodynamic diameter, which is related to the hydrodynamic drag of particles . These equivalent diameters do not provide any insight into the particle geometry and therefore, do not contain sufficient information to access functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1D space, nonspherical particles are typically described by equivalent size parameters such as the volume equivalent diameter, diameter of equal volumespecific surface area, or the hydrodynamic diameter, which is related to the hydrodynamic drag of particles. [32] These equivalent diameters do not provide any insight into the particle geometry and there fore, do not contain sufficient information to access functional properties. The investiga tion of nonspherical particles requires the description of their shape and distributions.…”
Section: Introductionmentioning
confidence: 99%